KARAKTERISTIK KEKUATAN OTOT, KELENTURAN TUBUH, KOMPOSISI TUBUH DAN INDEKS MASSA TUBUH SISWA SMK NEGERI 5 DENPASAR TAHUN AJARAN 2014/2015 - Dhivya Reddy Ramadas (DiscoverSys Inc., 2016)
BackgroundSomeone has a good level of fitness when exercising 3-5 times a week, and allocate 3 hours of lessons in physical education curriculum structure while the implementation of physical education in SMK Negeri 5 Denpasar allocate training time which is 1 times a week with a duration of 60 minutes.PurposesTo determine the physical status of the aspects of muscle strength, body flexibility, body composition, and body mass index of students of SMK Negeri 5 Denpasar.MethodsThis study is a quantitative descriptive research to determine the physical status of muscle strength, muscle tone, body fat composition, and body mass index in the students of SMK Negeri 5 Denpasar. The sample of this study were 43 students.ResultAverage of the left hand grip strength 28.48 ± 14.243; right-hand grip strength 26.49 ± 17.069; the strength of the back muscles 89.83 ± 40.921; leg muscle strength 74.49 ± 37.861. Body flexibility obtained an average of 6.42 ± 5.343. Body fat composition obtained an average 11.82 ± 3.589. The average body mass index of 20.97 ± 1.992.ConclusionFrequency of sample exercises mostly only 1 time per week. The duration of most of the 1-hour exercise in one workout. Most have poor and very poor muscle strength. Most men have average body flexibility and good. Most women have a average body flexibility. The composition of body fat on average at 11.82 ± 3.58. Most subjects had a normal body mass index.